New data of two Mylonchulus species (Mononchida: Mylonchulidae) and an updated key to species from Vietnam - Thanh Tam, Vu Thi (Academia Journal of Biology, 2016)
Two species of Mylonchulus, M. kermaniensis and M. oceanicus, were recorded, described and illustrated for the first time from Vietnam. Mylonchulus kermaniensis was collected from Nghe An province, their measurements and description correspond well with the type population from Kerma, Iran except for the absence of vulval papilla(e). Mylonchulus oceanicus was found in Cao Loc, Lang Son province. Measurements and description of the Vietnamese specimens fit well the type population from Hawaii, USA as well as another population from Japan except for a slightly shorter tail (c = 47-56 vs 39-49 in type and other population). In addition, an updated key to twenty already known species in Vietnam is also given in this paper.